National and international mergers in mixed oligopolies - Méndez Naya, José (Estudios de Economía, 2016)
Taking as a reference a model in which there are a public firm, a national private firm and a foreign private one, it is analyzed both mergers sustainability and their relative effects on welfare. It is proved that the merger between the public firm and either the national or the international private firm is preferred, from a welfare point of view, to the merger between the two private firms if the degree of privatization is relatively low and the foreign ownership of the merged firm is relatively high.